Association of health behaviors with function and health-related quality of life among patients with Parkinson's disease - Michal Duvdevani; Galit Yogev-Seligmann; Ilana Schlesinger; Maria Nassar; Ilana Erich; Rafi Hadad; Michal Kafri (BMC, 2024)
Abstract Background Current evidence on chronic conditions favors promotion of health behaviors as a mean to positively impact health outcomes. In Parkinson's disease, performing health behaviors is indicated as a means to fight the long-lasting burden of the disease. Understanding actual engagement in health behaviors and patient activation and their association to function and health-related quality of life is therefore important. Our objectives were, among people with Parkinson's disease: (1) to characterize health behaviors including utilization of rehabilitative treatments, physical activity, and patient activation levels, and (2) to test the associations between these health behaviors and health outcomes. Methods A cross-sectional study of 88 people with Parkinson's disease (age 66.84 ± 8.8) was conducted. Participants answered questionnaires measuring health behaviors including utilization of health professions treatments, physical activity, patient activation, and health outcomes consisting of function and health-related quality of life. Linear regression models were conducted to test associations between measured health behaviors, function and health-related quality of life. Results Participants rarely engage in rehabilitative treatments, but showed high levels of patient activation. Controlled by demographics and disease severity, physical activity and patient activation were associated with function (b = 0.41, p < .001; b = 0.2, p = .02, respectively) and physical activity but not patient activation, which was associated with health-related quality of life (b = 0.19, p = .03). There was also interaction effects of physical activity and non-motor symptoms, and physical activity and motor symptoms on health-related quality of life (b = 0.19, p = .02 and b = − 0.22, p = .01, respectively). Conclusions In respect to their potential health-related benefits for people with Parkinson's disease, health professionals' treatments are underutilized. Findings supported the importance of health behaviors for maintaining function and health-related quality of life among people with Parkinson's disease. They also show a differential contribution of motor and non-motor symptoms to the association between physical activity and quality of life. It is suggested that policy makers encourage opportunities for physical activity tailored for people with Parkinson's disease and adopt a proactive stance towards enhancing awareness and use of rehabilitation services. Trial registration NCT05211700, ClinicalTrials.gov ID: NCT05211700 first release 12/30/2021, https://classic.clinicaltrials.gov/ct2/show/NCT05211700